A visible-light activated [2 + 2] cycloaddition reaction enables pinpointing carbon–carbon double bonds in lipids. Issue 27 (30th June 2020) - Feng, Guifang; Hao, Yanhong; Wu, Liang; Chen, Suming
Abstract : A new visible-light activated [2 + 2] cycloaddition reaction was discovered and enabled pinpointing carbon–carbon double bonds in lipids. Abstract : The precise location of CC bonds in bioactive molecules is critical for a deep understanding of the relationship between their structures and biological roles. However, the traditional ultraviolet light-based approaches exhibited great limitations. Here, we discovered a new type of visible-light activated [2 + 2] cycloaddition of carbonyl with CC bonds. We found that carbonyl in anthraquinone showed great reactivities towards CC bonds in lipids to form oxetanes under the irradiation of visible-light. Combined with tandem mass spectrometry, this site-specific dissociation of oxetane enabled precisely locating the CC bonds in various kinds of monounsaturated and polyunsaturated lipids. The proof-of-concept applicability of this new type of [2 + 2] photocycloaddition was validated in the global identification of unsaturated lipids in a complex human serum sample. 86 monounsaturated and polyunsaturated lipids were identified with definitive positions of CC bonds, including phospholipids and fatty acids even with up to 6 CC bonds. This study provides new insights into both the photocycloaddition reactions and the structural lipidomics.